2021
DOI: 10.1177/21650799211003824
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Worker Violent Deaths in the Workplace: A Summary of Cases From the National Violent Death Reporting System

Abstract: Background: Violent workplace deaths among health care workers (HCWs) remain understudied in the extant literature despite the potential for serious long-term implications for staff and patient safety. This descriptive study summarized the number and types of HCWs who experienced violent deaths while at work, including the location in which the fatal injury occurred. Methods: Cases were identified from the Centers for Disease Control and Prevention’s National Violent Death Reporting System between 2003 and 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Workplace violence, while often resulting in injury, is usually not fatal (Occupational Safety and Health Administration, 2016). Nevertheless, healthcare workers can become victims of homicide both related to their work in healthcare (Braun et al, 2021) and outside of their work (Palmer et al, 2023; Robiner & Li, 2022; Robiner & Dorzinski, 2023). The epidemiology of health professionals' homicides has garnered limited attention (Goodman, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Workplace violence, while often resulting in injury, is usually not fatal (Occupational Safety and Health Administration, 2016). Nevertheless, healthcare workers can become victims of homicide both related to their work in healthcare (Braun et al, 2021) and outside of their work (Palmer et al, 2023; Robiner & Li, 2022; Robiner & Dorzinski, 2023). The epidemiology of health professionals' homicides has garnered limited attention (Goodman, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Although it is suggested that nurses have greater exposure to occupational violence and aggression, estimates are influenced by time spent with patients, differences in reporting, and contextual and sociological factors 3 . Alarmingly, several studies have reported health care staff being killed while on duty as a result of workplace violence 2,6,7 . Factors purported to influence violence against health care workers include context of practice, setting, or discipline 3 .…”
Section: Introductionmentioning
confidence: 99%
“…9 Consistent with patterns of violent death in the general population, healthcare workers are more likely to die by suicide than homicide. 15 A systematic review revealed that physicians are at risk for death by suicide and emphasized the need to implement studies investigating death by suicide in other healthcare professionals. 16 The rate of homicides of healthcare professionals also is alarming.…”
mentioning
confidence: 99%
“…The incidence of healthcare professionals who die by suicide has been estimated by some researchers to exceed rates in the general population 9. Consistent with patterns of violent death in the general population, healthcare workers are more likely to die by suicide than homicide 15. A systematic review revealed that physicians are at risk for death by suicide and emphasized the need to implement studies investigating death by suicide in other healthcare professionals 16…”
mentioning
confidence: 99%